Pemetaan Karakteristik Pola Belanja dan Konsumsi Makanan dan Minuman dalam Konteks Musiman (Ramadan): Implikasi Strategis bagi UMKM Wilayah Jabodetabek - Ekadipta Ekadipta; Chriswahyudi Chriswahyudi; Raga Patih Andika Putra; Babay Jutika Cahyana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Ramadan brings significant changes in the shopping and consumption patterns of Indonesians. There is an increase in demand for various types of food and beverages, both for sahur and iftar. The purpose of this study is to map the characteristics of food and beverage purchasing and consumption patterns in a seasonal context (Ramadan): strategic implications for UMKM in the Greater Jakarta area. The research design used is descriptive quantitative with data collection techniques implemented by distributing questionnaires. Then, the questionnaire answers are summarized to obtain the frequency distribution of each item in the questionnaire. The population of this study is people domiciled in the Greater Jakarta area. The sample size was determined using the Lameshow formula, resulting in a sample of 100 respondents spread across the Greater Jakarta area. The majority of respondents, namely 92%, stated that they experienced changes in their shopping patterns during Ramadan. The type of food purchased changed (34%) was the most dominant change. The most dominant consumption purchasing decision during Ramadan was the practicality in preparing food (40%), with favorite shopping places being traditional markets (24%) and street vendors (24%). In a consumption analysis, 83% of respondents experienced changes in their consumption patterns during Ramadan, with the most dominant change being in the amount of food consumed (29%). During sahur (pre-dawn meal), respondents tended to consume vegetables (36%) and chicken (22%). Meanwhile, fried foods (38%) and rice cakes (rice cakes) were the favorite dishes for breaking the fast.